Hyperbolic Expression in the Album NICOLE by NIKI - Yanti, Cita Hikmah; Muslimin, Zulvanul (Jetlal, 2024)
The research entitled hyperbolic expression in the album NICOLE by NIKI focuses on knowing the hyperbole that contained in the song lyrics in this album. The purpose of this research is to find the hyperbole formula based on claridge's theory and reveal the impact of using hyperbole in the album NICOLE by NIKI. The researchers used qualitative research in conducting the research. The data was collected from the song lyrics on the NICOLE album. The researchers found 7 hyperbole formulas contained in the song lyrics on the album NICOLE by NIKI, which are single-word hyperbole, phrasal hyperbole, clausal hyperbole, numerical hyperbole, the role of superlative, comparison hyperbole, and repetition.